KLAN POLITIK: STUDI TENTANG RIVALITAS CALEG KELUARGA PADJALANGI DAN HALID PADA PEMILU SERENTAK 2019 - Riswandi, Riswandi; Nurdin, Reskiyanti; Alamsyah, Anggriani (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2019)
This study discussed the orientation, behavior and strategy implemented by two clans, the Padjalangi clan and the Nurdin Halid clan, which were more focused on their children namely Andi Izman Maulana Padjalangi and Andi Muhammad Zunnun Armin Nurdin Halid who carried out rivalry in the 2019 simultaneous elections, DPRD Dapil Province 7 Regency of Bone. This study also used qualitative methods with descriptive analysis. Data collection used observation techniques, interviews, study of documents using political clan theory, behavioral approaches, voters and social capital. The results of this study indicated three variables in answering the formulation of the problem, namely: Izman Padjalangi Political Behavior was firmness in leading and popular behavior and the Political Behavior of Zunnun Halid was his attitude which was more inclined to resolve the problem by way of deliberation. Izman Padjalangi's political orientation was an increase in human resources. And Zunnun Halid's political orientation was the application of education. Izman Padjalangi's Political Strategy was socialization and orders to choose him who comes from his parents. And Zunnun Halid's Political Strategy was to approach the middle of the community, community leaders, religious leaders, customs, politics, youth and be the segmentation that was aimed by Zunnun and Izman to gain support in the midst of society.